Antibody Profiling in Naïve and Semi-immune Individuals Experimentally Challenged with Plasmodium vivax Sporozoites - Arévalo-Herrera, Myriam (PLoS Negl Trop Dis, 2016)
BACKGROUND: Acquisition of malaria immunity in low transmission areas usually occurs after relatively few exposures to the parasite. A recent Plasmodium vivax experimental challenge trial in malaria naïve and semi-immune volunteers from Colombia showed that all naïve individuals developed malaria symptoms, whereas semi-immune subjects were asymptomatic or displayed attenuated symptoms. Sera from these individuals were analyzed by protein microarray to identify antibodies associated with clinical protection. METHODOLOGY/PRINCIPAL FINDINGS: Serum samples from naïve (n = 7) and semi-immune (n = 9) volunteers exposed to P. vivax sporozoite-infected mosquito bites were probed against a custom protein microarray displaying 515 P. vivax antigens. The array revealed higher serological responses in semi-immune individuals before the challenge, although malaria naïve individuals also had pre-existing antibodies, which were higher in Colombians than US adults (control group). In both experimental groups the response to the P. vivax challenge peaked at day 45 and returned to near baseline at day 145. Additional analysis indicated that semi-immune volunteers without fever displayed a lower response to the challenge, but recognized new antigens afterwards. CONCLUSION: Clinical protection against experimental challenge in volunteers with previous P. vivax exposure was associated with elevated pre-existing antibodies, an attenuated serological response to the challenge and reactivity to new antigens.